Dose-dependent severe cutaneous reactions to imatinib - Ugurel, Selma; Hildenbrand, Ralf; Schadendorf, Dirk (British journal of cancer, 2003)
The protein kinase inhibitor imatinib has been approved as an efficient anticancer drug with common but mild cutaneous toxicities. We here report on two out of four melanoma patients treated with high-dose imatinib presenting with severe and strongly dose-dependent skin eruptions, suggesting a cutaneous reactivity pattern different from allergic hypersensitivity.